Avaliação do microclima urbano para a cidade de Sorriso/MT : estudo de caso - França, Mauro Sergio de (2017)
The cities of the Middle-North of Mato Grosso underwent an intense urbanization process, starting in the 1990s, implying changes in land use and regional coverage. These changes affected the cities of the region, one of these impacts being the local thermal comfort conditions, especially in densely built urban areas, notably in the central region. Therefore, this study aimed to evaluate the application of two thermal comfort indexes in the central area of the city of Sorriso, State of Mato Grosso, using the mobile transect method. It was defined a route in the urban perimeter prioritizing the main avenues of the central region of the city. In this route, air temperature and relative humidity data we collected, with intervals every 6 seconds for each collection. There were 30 days of collection, 15 days in the hot-dry season, between August and September 2015 and 15 days in the hot-humid season, between January and February 2016, respecting the regional seasonality. The collections started at 20:00 local time (00:00 UTC), with 25 minutes the average time of a route. The measured data we used to calculate the two thermal comfort index: the Temperature and Humidity Index (THI) and the Heat Index (HI). These indices we analyzed statistically, validated by semivariograms and spatialized in the study area, using ordinary kriging interpolator. The results observed during the hot-dry season showed a predominance of slightly uncomfortable days for UTI and of caution for HI. In the hot-humid season, there were slightly uncomfortable days for the ITU and comfortable days for the IC. It was concluded that the environmental conditions are worrying in the city, specifically with respect to thermal comfort, since it was identified that the applied indices were different in the stations, pointing out that the land use differentiated allied to the regional seasonality contributed for the variations of the microclimatic conditions, being more unpleasant, on average, in the first mentioned station.